Analysis of Urban Infrastructures and Facilities in Pakhribas Municipality, Dhankuta, Nepal (The Geographic Base, 2021)
The study presents condition of spread of urban infrastructures to over the Pakhribas municipality, Dhankuta, Nepal. Both the primary and secondary data were used for the study. Secondary data was collected from municipal profile of Pakhribas municipality and the primary data i.e., field observation, household questionnaire survey and focus group discussion were carried out for identify existing condition of the physical infrastructure, the access of the local people to the infrastructure, and the expectation of the dwellers with the municipality. Statistical analysis was preformed through arithmetic mean, population density and infrastructure development index. The result shows ward number four has the highest population density, and the people have more access to urban facilities including heath facilities and schools. The rest wards of the municipality have similar condition with its neighboring rural municipalities in terms of infrastructures and facilities. Among the total households most of them (90.45%) use pipe water for drinking. Most households (95.02%) use hydroelectricity. Most of the area of municipality 48 have easy access for the transportation with different status of road i. e. feeder road, district road and Highway. There have eight recreation centers within the municipality, which prompted domestic tourism in the region. The information screened through this study provided the overall infrastructure and facilities status of the municipality.